POPULATION AGEING IN THE MURCIA REGION (II) - Gómez Fayrén, J.; Bel Adell, C.; Montaner, E.; Marcos, M.D. (Geography Papers, 1995)
This article is the second of two parts. The first one was published in the issue no 2 of this same journal. The preseni study uses the dependency index and the youth ratio to describe the aging process both at regional and municipal levels. Our data show a yet moderate aging process in (he region. with an uneven distribution throughout the different municipalities.